Challenges of Medical Education in Libya: A Viewpoint on the Potential Impact of the 21st Century - Elkhammas, Elmahdi A.; Al-Areibi, Arif; Rajab, Faten Ben; Arrabti, Abdelaziz (Ibnosina Journal of Medicine and Biomedical Sciences, 2023)
Traditional medical education is no longer adequate for preparing medical graduates for immediate practice and to make them ready to practice their profession efficiently with quality and citizenship to the health care system. Medical education is changing based on changes in societies, culture, technology, and quality of care. More elderly patients require special attention, technologies require different skills, and patient-centered, evidence-based medicine needs special training. In Libya, an example of a developing country, medical education faces these challenges and many more. It requires ample resources and an adequate number of qualified health care professionals who are highly specialized. Such faculty are up to date to deliver service, teach, and perform quality research. Attention is necessary to improve their medical education system and keep up with the advances and care needed for their citizens. It is possible with more investment in faculty development, collaboration with reputable institutions in developed countries, and use of professional accreditation from international organizations.
Keywords: 21st century; developing countries; education; Libya; medical education; viewpoint